Fake news: Susceptibility, awareness and solutions - Tiziana Assenza; Alberto Cardaci; Stefanie J. Huber (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2024)
This paper investigates and quantifies citizens' susceptibility to fake news and assesses, using a randomized control trial, the effectiveness of a policy intervention to raise awareness. We find that the average citizen lacks proficiency in identifying fake news and harbors an inflated perception of his/her ability to differentiate between true and fake news content. Increasing awareness by providing information about personal susceptibility to fall for fake news causally adjusts individuals' beliefs about their fake news detection ability. Most importantly, we show that the simple intervention of informing citizens about their personal susceptibility to fall for fake news causally increases their willingness to pay for the fact-checking service.
Keywords: C83; D83; D84; D91; 330; Fake news; misinformation; disinformation; fact checking; information provision experiments; belief updating; willingness to pay